IKHTILAT DALAM PRESPEKTIF SYARIAT : BAHAYA, BATASAN DAN KONTEKS SOSIAL MODERN - Pratama, Dika Aji (AL HUKMU: Journal of Islamic Law and Economics, 2025)
This article examines the phenomenon of ikhtilat (mixing between non-mahram men and women) from the perspective of Islamic law, accompanied by a description of the dangers and limitations and conditions that allow it in modern society. This study is motivated by the increasing social interaction between genders in public spaces, education, the world of work, and social media. This research is qualitative with a literature study method from primary and secondary sources such as the Qur’an, hadith, tafsir books and the opinions of classical and contemporary scholars. Based on the results of the study, it is known that the mixing of non-mahram men and women results in violations of slanderous matters that damage morals. All Islamic jurisprudence scholars agree that ikhtilat is basically not permitted in a society except in certain conditions, such as in education, medicine, work and emergencies, with sharia requirements such as lowering the gaze, covering the genitals, behaving, not being alone together, and avoiding khalwat. This article is dedicated to the community, especially non-mahram men and women, to understand and practice social etiquette in accordance with Islamic law and experience changes in the understanding of the boundaries of ikhtilat which can be said to be modern.